Empirical investigation into impact of IT adoption on supply chain agility in fast food sector in Pakistan - Farwa Qureshi; Abida Ellahi; Yasir Javed; Mobashar Rehman; Hafiz Mudassir Rehman (Cogent Business & Management, 2023)
Information technology and supply chain agility are in vogue. The present study aims to investigate the impact of information technology (IT) on supply chain agility and its outcomes such as cost reduction and operational performance in fast food companies' chains. A total of 240 employees from fast food chains were selected as respondents. Data was collected using five-point Likert scale questionnaire developed from previous studies. The statistical results confirmed that adoption of IT is playing a vibrant role in achieving supply chain agility and supply chain agility helps to reduce cost and improves operational performance of firms. The study model provides a useful framework to examine the impact of IT adoption on supply chain agility and its outcomes. In conclusion, the firms have to focus on their supply chain management and make it efficient and agile by implementing the advanced technologies to gain operational performance. Implications have been discussed.
Keywords: 650; supply chain management; operational performance; cost reduction; IT adoption; supply chain agility